The English Plastic Bag Charge Changed Behavior and Increased Support for Other Charges to Reduce Plastic Waste - Thomas, Gregory Owen; Sautkina, Elena; Poortinga, Wouter; Wolstenholme, Emily; Whitmarsh, Lorraine (Frontiers in Psychology, 2019)
Plastic bags create large amounts of waste and cause lasting environmental problems when inappropriately discarded. In 2015, England introduced a mandatory five pence (US0.06/€0.06) charge to customers for each single-use plastic bag taken from large stores. Combining a longitudinal survey (n=1,230), supermarket observations (n=3,762), and a longitudinal interview study (n=43), we investigated people’s behavioural and attitudinal responses to the charge. We show that all age, gender, and income groups in England substantially reduced their plastic bag usage within one month after the charge was introduced, with interviewees highlighting the ease of taking their own bags. Support for the bag charge also increased among all key demographic groups. Increased support for the plastic bag charge in turn predicted greater support for other charges to reduce plastic waste, suggesting a ‘policy spillover’ effect. Results indicate a broad and positive effect of the bag charge, which appears to have catalysed wider waste awareness among the British public. This may facilitate the introduction of other policies to eliminate avoidable single-use plastics and packaging.